Red, gred, agred congestion control algorithms in heterogeneous traffic types - Seifaddini, Omid (UUM College of Arts and Sciences, Universiti Utara Malaysia, 2013)
There are several Active Queue Management algorithms (AQM) exist to deal with the congestion at the router buffer such as RED, DRED, BLUE, AGRED. This paper presents an analysis of RED, GRED and AGRED algorithms with three different Traffic distributions which are Exponential distribution, Geometrical distribution and ON-OFF model using simulation. The performance metric used to show the analysis of these algorithms with mentioned distributions is Packet Loss (Pl). Results of simulation show that each algorithm performed a fair dropping of data packets without considering of their types.